A Sport Education teaching unit as a citizenship education strategy in Physical Education. A group-randomized controlled trial (Una unidad didáctica de Educación Deportiva como estrategia de educación para la ciudadana en Educación Física. Un ensayo contr - Jesús Viciana; Carolina Casado-Robles; Laura Pérez-Macías; Daniel Mayorga-Vega (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The purpose of the present study was to examine the effect of a Physical Education (PE)-based Sport Education (SE) program on personal and interpersonal variables, social environment, and the predisposition of acquiring positive habits and autonomy in high school students in order to assess the contribution of this model to the students’ citizenship education. A sample of 123 adolescents, 60 boys and 63 girls, participated in the present study. Students were divided into one control (CG) and one experimental (EG) group. EG performed 12 PE-lessons of SE intervention based on volleyball small-sided games and educational competitions. CG followed a traditional treatment of sport in PE, mixing tasks with small-sided games and direct instruction methodologies. Results showed that EG participants had a statistically significant increase in the scores of the following dimensions: personal (the self-determined motivation toward PE, satisfaction/enjoyment toward sport, and the physical self-concept); interpersonal (relatedness with others, cooperative learning, and important role within a work-group); social (PE classroom climate, and sportspersonship); and autonomy and acquisition of habits (autonomy support, and the intention to be physically active) compared with the CG (p < .001). A SE intervention in PE will allow teachers to improve students’ citizenship competences. •